Digital geoarchaeology: bridging the gap between archaeology, geosciences and computer sciences - Siart, Christoph; Forbriger, Markus; Bubenzer, Olaf (Digital geoarchaeology, 2018)
Modern archaeology increasingly crosses academic boundaries by combining different new methodologies in order to answer research questions about ancient cultures and their remains. Above all, the geosciences became an indispensable counterpart of archaeology and cultural heritage management. As to the investigation of past archaeological landscapes and palaeoenvironments, the term Geoarchaeology is commonly used, representing the utilization of traditional and the development of new geoscientific applications for archaeological purposes. In addition, computationally engaged research became absolute state of the art in modern archaeology, in geoscientific landscape reconstructions and in the deciphering of spatio-temporal interactions between man and nature. Despite this multidisciplinary constellation, the thematic and methodological overlap of humanities, natural sciences and informatics is frequently disregarded. It is beyond debate that multidisciplinary approaches, which especially emerge at the interface of adjacent subjects, substantially contribute to a better understanding of ancient landscapes, their forming processes and the resulting cultural heritage. They allow fusing complementary perspectives for the first time and therefore go far beyond unilateral research designs. Digital Geoarchaeology, which is to be established in this chapter as a new concept for the first time, can therefore be regarded as an intersection of disciplines that contributes to the consolidation of different academic perspectives. It represents a novel approach in terms of computer scientific methods combined with geoscientific know-how and archaeological expertise to multi-methodically investigate past human-environmental relationships. Accessing this multidisciplinary interface helps overcome potentially restricted, monodisciplinary perceptions and provides new forms of unbiased approaches for investigating the interplay of man and nature. Thus, closer collaboration and dialogue across disciplinary boundaries will offer promising prospects for future research at the human-environmental interface.
Gesehen am 27.07.2022